Star Wars. [compact disc, unabridged] The force unleashed II - Williams, Sean, 1967- (Star wars., 2010)
Starkiller, who Darth Vader personally trained to assassinate Emperor Palpatine, is brought back from the abyss of death and reprogrammed to kill anything that gets in the Empire's way. However, Starkiller's love for Juno Eclipse may prove to be a stronger bond than the enslaving chains of the Dark Side.